Batak Muslim Local Wisdom: Sociological Analysis of Buffalo Slaughtering Tradition of Angkola Community Death Ceremony - Arbanur Rasyid; Rayendriani Fahmei Lubis; Maulana Arafat Lubis; Nashran Azizan (Institut Agama Islam Negeri Kendari, 2022)
This research examines the local wisdom built by the Muslim community of Angkola around the ritual of slaughtering buffalo in the event of death ceremony. This study is a field research combining observation, interviews, and document analysis with a sociological analytical technique to evaluate the tradition beginning with the reasons for its adoption, the process, and the desired outcomes. The study’s findings indicate that the Angkola people’s practice of slaughtering buffalo in burial ceremonies is motivated by a desire to preserve traditional culture as well as a means of protecting the social strata of traditional elders. Furthermore, this ritual appears to be a technique of sustaining societal social cohesiveness. The buffalo slaughter served as the foundation for implementing Islamic ideals in an atmosphere of brotherhood and generosity, with Mora Khanggi and Anak Boru serving as the primary funders. The outcomes of the study demonstrate that the practice of local communities as part of life knowledge can be sociologically connected with Islamic theological teachings. Acculturation of culture with religious teachings can genuinely present various choices for propagating religion while also exhibiting theological flexibility in order to make it more welcoming to its devotees.